1991
DOI: 10.6013/jbrewsocjapan1988.86.293
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Determination of Protein Bodies (PB-I, PB-II) in Polished Rice Endosperm

Abstract: A was ordinary commercial rice and B was rice suitable for sake brewing. Ave. and S. D. were described in Table 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…On the other hand, Kizaki et al (1991) examined the protein content of grains of Yamadanishiki and Gohyakumangoku with various polishing rates, and found that the central region had fewer storage proteins than the peripheral region.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Kizaki et al (1991) examined the protein content of grains of Yamadanishiki and Gohyakumangoku with various polishing rates, and found that the central region had fewer storage proteins than the peripheral region.…”
Section: Introductionmentioning
confidence: 99%
“…For analysis of the protein body (PB), we followed the method reported by Kizaki et al 12) The PB was detected by SDS-PAGE, and PB composition (%) was calculated from the peak area on densitograms using an imaging system (Gel Doc EZ Imager, Bio-Rad Laboratories, Inc., USA).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, PB-II has a large effect on the amino acid content of brewed sake while PB-I has only a small effect (Wakai et al, 1997;Mizuma et al, 2002). Rice suitable for sake brewing has a higher PB-II/PB-I ratio than rice for cooking, and the suitability for sake brewing can be characterized by protein composition (Kizaki et al, 1991(Kizaki et al, , 1993Ohdoi et al, 2000;Iwano et al, 2001).…”
mentioning
confidence: 99%
“…There are two types of PB, PB-I and PB-II, and prolamin is localized in PB-I and glutelin in PB-II (Tanaka et al, 1980). PB-I has a fi rm structure and hardly digested by koji yeast (Kizaki et al, 1990;Kizaki, 1999;Furukawa et al, 2000) and occupies about 23% of total protein in 70%-polished rice (Kizaki et al, 1991). On the other hand, PB-II occupies about 60% of total protein in 70%-polished rice (Kizaki et al, 1991).…”
mentioning
confidence: 99%
See 1 more Smart Citation